Why Do Firms Suffer Differently from Input Stigmatization? The Costs of Removing Stigmatized Inputs - Diestre, Luis; Santaló, Juan (Organization Science, 2020)
Firms using stigmatized inputs are likely to experience strong pressures from multiple stakeholders who demand removal of such inputs from firm operations. Consistent with this phenomenon, we propose that greater levels of input stigma decrease firm performance and that firms respond to this threat by reducing the use of such inputs. However, we argue that not all firms are equally able to remove stigmatized inputs. Firms with a high degree of input overlap among their product units will be less likely to remove stigmatized inputs from their operations; as such, a change could be costlier for them. Consequently, we propose that firms facing high input overlap will experience the negative effects of input stigma more strongly. We find support for our theory by looking at toxic chemicals as the inputs that may become stigmatized.